2021
DOI: 10.1039/d1an00981h
|View full text |Cite
|
Sign up to set email alerts
|

A study of the application of graphite MALDI to the analysis of lanthanides and deconvolution of the isobaric species observed

Abstract: Matrix-assisted laser desorption/ionisation mass spectrometry has always suffered from matrix interference at low-masses making it an unsuitable method for the analysis of low molecular weight analytes. In recent years, there...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…110,111 In another study, colloidal graphite was successfully used for the identification of lanthanides and their oxidized species. 112 Graphite has long been used as an adsorbent to extract a variety of nonorganic materials, such as heavy metals and organic compounds such as pollutant dyes, to separate the impurities from samples. 113,114 Such a property stems from the high surface area of graphite particles that can be increased further when the particle size is reduced to the nanometer range.…”
Section: ■ Carbon Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…110,111 In another study, colloidal graphite was successfully used for the identification of lanthanides and their oxidized species. 112 Graphite has long been used as an adsorbent to extract a variety of nonorganic materials, such as heavy metals and organic compounds such as pollutant dyes, to separate the impurities from samples. 113,114 Such a property stems from the high surface area of graphite particles that can be increased further when the particle size is reduced to the nanometer range.…”
Section: ■ Carbon Nanotubesmentioning
confidence: 99%
“…The results showed that colloidal graphite produced reproducible spectra with minimal low-mass matrix interferences and was able to detect PEG molecules as small as dimers . The relatively stable suspension of colloidal graphite produces a smooth and homogeneous film on a MALDI plate after drying, leading to the generation of reproducible results. , In another study, colloidal graphite was successfully used for the identification of lanthanides and their oxidized species …”
Section: Graphitementioning
confidence: 99%
“…Among the materials used for LDI-MS, carbon has a series of allotropes (e.g., graphite, 13,14 graphene, 15−17 graphdiyne, 18 carbon nanotubes, 19,20 and fullerene 21 ) that exhibit high thermal and electrical conductivities, low heat capacities, and excellent UV absorption abilities. These characteristics are strongly related to the efficiency of the LDI process and ensure that carbon-based nanomaterials are often used as surface substrates for SALDI-MS. Graphite, in particular, one of the most promising materials, has been designed (colloidal graphite) to detect low-molecular-weight compounds, such as lanthanides and their oxides 22 and polyethylene glycols. 23 In our previous study, we successfully accomplished the simultaneous detection of taste-and odor-active compounds using graphite carbon black (GCB) 24 and demonstrated that graphite-assisted SALDI-MS can be utilized in small-molecule analyses and measured in positive and negative modes simultaneously compared with using a conventional organic matrix.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among the materials used for LDI-MS, carbon has a series of allotropes (e.g., graphite, , graphene, graphdiyne, carbon nanotubes, , and fullerene) that exhibit high thermal and electrical conductivities, low heat capacities, and excellent UV absorption abilities. These characteristics are strongly related to the efficiency of the LDI process and ensure that carbon-based nanomaterials are often used as surface substrates for SALDI-MS. Graphite, in particular, one of the most promising materials, has been designed (colloidal graphite) to detect low-molecular-weight compounds, such as lanthanides and their oxides and polyethylene glycols …”
Section: Introductionmentioning
confidence: 99%